Multiple binding sites miRNA with mRNA of human genes (Experimental biology, 2015)
We searched the structural organization of binding sites miR-3960, miR-3620-5p and miR-8072 in the mRNA of human genes. Identified sites mRNA in which through 1-5 nucleotides several binding sites of miR-3960 are located. The nucleotide sequences of these sites in the CDS encode polyalanine or polyproline. In 5’UTR and 3’UTR structural organization of miR binding sites identical to that in the CDS. Shown that miR-3960, miR-3620-5p and miR-8072 can bind with genes involved in cell cycle regulation and apoptosis. Discusses the properties of miR-3960, miR-3620-5p and miR-8072 and their role in the development of cancer.
Keywords: miRNA; mRNA; nucleotides; binding sites; target genes